Metadiscursive Features in Research Articles: The Role of Stimulated Recall - Rajab Esfandiari; Omid Allaf-Akbary (Journal of English Language Teaching and Learning, 2022)
While metadiscourse has been extensively examined across several genres, contexts of publication, disciplines, and languages over the past two decades, researchers have mainly limited themselves to the qualitative checking of candidate metadiscourse markers for the various functions they serve. In the present study, however, we drew on retrospective methods coupled with semi-structured interviews to gain a deeper understanding of metadiscourse features applied linguistics apprentice and professional authors use in their research articles (RAs) in national and international English-medium journals. To achieve this goal, we built on Hyland’s (2019) interpersonal metadiscourse model to analyse RAs in three subsections including introductions, results, and discussion. We ran chi-square tests to examine the RA variations, following the descriptive analysis of the use of metadiscourse markers. A follow-up stimulated recall through semi-structured e-mail interviews was used. We used MAXQDA to analyse the interview data from authors. The results of qualitative and thematic analyses showed that metadiscourse markers play key roles in conveying the writers’ message and intention to the members of discourse communities. The findings of the study suggest raising apprentice writers’ awareness of the way they frame their message in research writing